The greedy book - Schloesser, Frank, -1913 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Greedy Book: A Gastronomical Anthology" by Frank Schloesser is a collection of essays on culinary arts and gastronomy written in the early 20th century. This anthology explores the joy of eating and drinking, touching upon the cultural significance and artistry involved in cookery, as well as reflections on cookery throughout history. Readers will likely find it engaging if they have an interest in the history of food, culinary practices, and gourmet cuisine. The opening of "The Greedy Book" sets the tone for a whimsical yet insightful exploration of the culinary world. The text begins with a quote praising the pleasures of eating and the human digestive system, immediately establishing its thematic focus on gastronomy. Schloesser presents thoughts on the artistry of cooking, the importance of understanding flavors, and the historical context surrounding notable chefs and their contributions to the culinary landscape. Additionally, there are humorous anecdotes about the perspectives of cooks, patrons, and diners, suggesting that both food and the experience of dining carry profound cultural implications. The initial chapters delve into the essence of cookery, the character of chefs, and delightful discussions around the intricacies of meal preparation, setting a rich tableau for the anthology that follows. (This is an automatically generated summary.)
Release date is 2024-06-12
Carol Brown, Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Gastronomy